It made my life a little easier: Primary care providers’ beliefs and attitudes about using opioid treatment agreements - Starrels, MD, MS, Joanna L.; Wu, MS, Bryan; Peyser, BA, Deena; Fox, MD, MS, Aaron D.; Batchelder, MA, MPH, Abigail; Barg, PhD, MEd, Frances K.; Arnsten, MD, MPH, Julia H.; Cunningham, MD, MS, Chinazo O. (Journal of Opioid Management, 2014)
Objective: To understand primary care providers (PCPs)’ experiences, beliefs, and attitudes about using opioid treatment agreements (OTAs) for patients with chronic pain. Design: Qualitative research study. Participants: Twenty-eight internists and family medicine physicians at two health centers. Approach: Semistructured telephone interviews, informed by the Integrative Model of Behavioral Prediction. Themes were analyzed using a Grounded Theory approach, and similarities and differences in themes were examined among OTA adopters, nonadopters, and selective adopters. Results: Participants were 64 percent female and 68 percent white, and practiced for a mean of 9.5 years. Adoption of OTAs varied: seven were adopters, five were nonadopters, and 16 were selective adopters. OTA adoption reflected PCPs’ beliefs and attitudes in the following three thematic categories: 1) perceived effect of OTA use on the therapeutic alliance, 2) beliefs about the utility of OTAs for patients or providers, and 3) perception of patients’ risk for opioid misuse. PCPs commonly believed that OTAs were useful for physician self-protection, but few believed that they prevent opioid misuse. Selective adopters expressed ambivalent beliefs and made decisions about OTA use for individual patients based on both observed data and a subjective sense of each patient’s risk for misuse. Conclusions: Substantial variability in PCP use of OTAs reflects differences in PCP beliefs and attitudes. Research to understand the impact of OTA use on providers, patients, and the therapeutic alliance is urgently needed to guide best practices.